Peran Guru Pendidikan Agama Islam sebagai Agen Dakwah Toleran di SDN 2 Margasari - Bubun Munawar Burhanudin; R. Riana Yuhansyah; Neneng Sugiharti; Eva Aprianti; Ai Yuni Haryani; Ati Ahyati; Imam Asrofi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to examine in depth the role of Islamic Religious Education (PAI) teachers as agents of tolerant da‘wah based on Islam Nusantara within multicultural elementary school settings. The research was conducted at SDN 2 Margasari, Pasawahan District, Purwakarta Regency, West Java, which represents the social, cultural, and religious diversity of students. This study employed a qualitative approach using a case study method to obtain a comprehensive understanding of PAI learning practices oriented toward tolerance values. Data were collected through in-depth interviews with PAI teachers and the school principal, direct observations of classroom PAI learning activities, and document analysis of religious programs and activities implemented at the school. The results indicate that PAI teachers play a strategic role in instilling values of tolerance, religious moderation, mutual respect, and appreciation of local wisdom through the application of dialogical, contextual, and inclusive learning methods. The learning strategies applied include the use of local stories and traditions that align with the values of Islam Nusantara, as well as the habituation of tasamuh (tolerance) attitudes in daily interactions within the school environment. This study recommends strengthening the competencies of PAI teachers in understanding and applying the Islam Nusantara approach, as well as integrating values of religious moderation into the elementary school curriculum as a systematic effort to build a culture of tolerance in multicultural educational settings.